Kinetics of radical formation during the mechanical activation of quartz - Damm, Cornelia; Peukert, Wolfgang (Langmuir, 2009)
The kinetics of radical formation during the mechanical activation of quartz by wet grinding or sonication was investigated using 2,2-diphenyl-1- picrylhydrazyl (DPPH) as a scavenger. The consumption of DPPH during the sonication of quartz in an ethanol suspension is a zeroth-order process. A linear relationship between the rate constant of the DPPH consumption and the quartz concentration in the suspension indicates that radical formation under sonication increases with the growing total surface area of the quartz particles. Sonication leads to the formation of free radicals by the mechanical activation of the particle surface. The kinetics of the DPPH consumption during wet grinding of quartz in a stirred media mill is described successfully by a modified zeroth-order rate law taking the total surface area of the quartz particles into account. The surface-normalized rate constant of the DPPH consumption decreases from 1.8 × 10 mol L h m to 4.8 × 10 mol L h m if the specific surface area of the feed material increases from 0.5 to 84 m/g. This finding indicates that the breakage of the quartz particles contributes much more to radical formation than does the mechanical activation of the particles in the mill because the breakage rate increases with growing particle diameter. Ethanol but not DPPH was found on the surface of the ground quartz particles. From this finding, it can be concluded that radicals on the surface of the quartz particles react with ethanol, leading to the formation of ethanol radicals and H radicals. DPPH reacts with the H radicals. As a side reaction, radicals can react with oxygen, leading to the formation of peroxides. © Copyright 2009 American Chemical Society.